Altered Salivary Flow, Protein Composition, and Rheology Following Taste and TRP Stimulation in Older Adults - Pushpass, Rose-Anna Grace; Daly, Blánaid; Kelly, Charles; Proctor, Gordon; Carpenter, Guy Howard (Frontiers in Physiology, 2019)
Taste and smell perceptions diminish in older age, impacting upon quality of life and nutrition yet the causes of taste loss are largely unknown. Transient receptor potential channels (TRP) found on the oral mucosa are also involved in oral sensations including cooling and burning and may contribute to the eating experience of older people. Older adults often have reduced salivary flow and the physical properties of saliva may change, but the role of saliva in oral sensations of older adults is yet to be elucidated. Here, the effect of older age on subjective (perception) and objective (stimulated salivary response) measures of TRP stimulants, odours and basic tastants was investigated. Whole mouth saliva was collected from younger (mean age 24 years) and older adults (mean age 72 years) following stimulation of taste (MSG and caffeine), olfaction (menthol) and TRP receptors (capsaicin). Participants rated perceived intensity of each stimuli and salivary properties were assessed. Older age was associated with 15% lower umami taste and 26% lower menthol odour perception, coupled with 17% lower salivary response to MSG. Interestingly there were no differences for perception of TRP stimulants, so chemo-sensation was not affected by age. Younger adults had 4 times greater elasticity (Spinnbarkeit) with MUC7 levels almost double and 66% greater resting salivary flow rate. Stimulated salivary responses in the younger group were also higher compared to the older group, with changes in protein and viscoelasticity in response to taste and TRP stimulation. These results show the impact of older age upon taste and smell sensation which may lead to changes in the physical and compositional properties of saliva in response to taste/odour stimulation. Measurement of stimulated salivary flow and rheology provides an objective measure of taste in addition to subjective perceptions which can be influenced by participant bias. Chemo-sensation may be retained with age and trigeminal stimuli such as chilli could be employed in future studies to enhance meals for an age group at risk of malnutrition. Alteration in salivary properties due to advanced age could impact on ability to taste due to poor diffusion of tastants and reduced oral surface protection.